“Esse menino não come”: narrativas de mães sobre seletividade alimentar e autismo - Uchoa, Brunna Karoliny Pereira (2024)
Eating difficulties are increasingly present in childhood, among them, food selectivity stands out, understood as a limited intake of a variety of foods and refusal of most new foods and nutrients. Although it can manifest itself in any child, there is a higher prevalence of cases in children with autism. The experience of being and eating together for families of children with autism and food selectivity is challenging and perceived by many parents as stressful, exhausting and chaotic. The objective of this study is to understand maternal representations about the food selectivity of their children with autism. This is a phenomenological research with a qualitative approach carried out with mothers of children diagnosed with autism and who present food selectivity, followed in a secondary care unit aimed at this population. Data collection took place through in-depth interviews conducted individually and in person. Data analysis was performed through Bardin's Thematic Content Analysis. The analysis process led to the structuring of five categories and fifteen subcategories. The themes highlighted content such as the emergence of children's eating problems, which began early during breastfeeding and the introduction of solid foods, followed by the mother's search to find a name for the differences perceived in her children. The main difficulties presented by the children were brought to light, along with the mother's feelings and perceptions regarding mealtimes with the child and the overload of care that the occupational role of mother demands. In addition, the themes cover beliefs surrounding the child's diet and the strategies used to feed the children. Expectations regarding the future, desires and fears arising from it and related to food selectivity or the children's autism are perceived and associated with conditions of stress, depression and anxiety. And last but not least, the support network that is present in the lives of these women, and the quality of this support, with family support, spouses and close relatives, perceived as insecure. In contrast, the social support found in proximity to other women experiencing the same situation was perceived as substantial. The study concludes that food selectivity causes maternal exhaustion, abandonment of occupational roles, psychological suffering and is disruptive to family life. Therefore, identifying risk signs with early and assertive interventions is necessary for positive outcomes.